Soul/Spirit Concept in Yunus Emre’s Poems - Yalçınkaya, Fatoş (Journal of Alevism-Bektashism Studies, 2021)
The theme of soul/spirit occurs frequently in the poems of Yunus Emre, one of the great poets of the Turkish world. In Yunus Emre’s poems, soul is related to death. In his death-themed poems, the concept of soul/spirit is sometimes obvious and sometimes hidden. For Yunus, death is not something to be afraid of; on the contrary, it means reaching to a beloved, a friend. To die is the disappearance of the body, and the meeting of the soul with the friend because the material that dies is the body. The soul/spirit is immortal. Death is the liberation of the soul from the body in which it is imprisoned.The paper discusses the soul/spirit theme in the poems from Yunus Emre Divan. Based on Yunus Emre’s poems, while analysing what he meant by the concept of soul, concepts such as death and spirit, both related to soul, are also included in order to better understand the concept of soul.The study gives the information about the life and works of Yunus Emre by using historical sources. Afterwards, it mentions the studies on Yunus Emre related to our research subject. The examples are taken from the e-book Dîvân-ı Yunus Emre prepared by Mustafa Tatci for the Ministry of Culture and Tourism. We used the same numbering as in the book itself. In order to better understand the soul/spirit metaphor that Yunus Emre used in his poems, the study includes the opinions on the use of this metaphor from domestic and foreign sources. The flight of soul, the relationship between soul and death, and the cage-bird relationship are briefly discussed. It has been determined that all these terms evoke death.After analysing Yunus Emre’s poems, it occurs that he didn’t initially accept death. However, his attitude towards death is obvious. Nevertheless, Yunus doesn’t just look at the world through his own eyes, he also sees it through the eyes of others. In fact, he is a guide to those who fear death, during their journey. The death means reaching ultimate union, reuniting with beloved.
Keywords: Yunus Emre; poetry; soul; spirit; death